Borrowed names : poems about Laura Ingalls Wilder, Madam C. J. Walker, Marie Curie, and their daughters - Atkins, Jeannine, 1953- (Square Fish, 2018)
Contains poems about the historical women Laura Ingalls Wilder, Madam C.J. Walker, and Marie Curie and their relationships with their daughters.